2002
DOI: 10.1590/s0066-782x2002000100002
|View full text |Cite
|
Sign up to set email alerts
|

Epworth's sleepiness scale in outpatients with different values of arterial blood pressure

Abstract: OBJECTIVE: To compare sleepiness scores of the Epworth scale in patients with different levels of arterial pressure when undergoing outpatient monitoring within the context of clinical evaluation. METHODS: A total of 157 patients selected for outpatient monitoring of arterial pressure during hypertension evaluation were divided into 3 groups: group 1 - normotensive; group 2 - hypertensive; group 3 - resistant hypertensive. For analysis, values > or = 11 were considered as associated with respiratory disturbanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
(19 reference statements)
3
6
1
3
Order By: Relevance
“…This finding is similar to that reported by other studies [27, 2931]. The absence of a difference may be as a result of repeated sympathetic nervous system firing during the day which maintains an alert and awake state.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is similar to that reported by other studies [27, 2931]. The absence of a difference may be as a result of repeated sympathetic nervous system firing during the day which maintains an alert and awake state.…”
Section: Discussionsupporting
confidence: 92%
“…In a study, ESS is not associated with resistant hypertension [46]. In another study, Gus also confirmed a positive relationship between the ESS and hypertension severity in patients >18 years of age; but after correcting for age, the results were not significant [47]. Though both these two studies contradict our independent correlations between ESS and hypertension, they had relative small sample size.…”
Section: Discussionmentioning
confidence: 83%
“…Patients did not have a full clinical examination and the differences did not reach statistical significance after controlling for confounders. 24 Assessing only daytime sleepiness by ESS may be very sensitive but not specific for the diagnosis of OSAS. Therefore, the association between this symptom and hypertension may be less intense.…”
Section: Discussionmentioning
confidence: 99%